1953
DOI: 10.1063/1.1721294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Very High Pressures on Glass

Abstract: In contrast to other inorganic solids, glasses may be permanently compacted by application of pressures of the order of 104 to 105 atmospheres. This effect was studied on two simple oxide glasses (SiO2 and B2O3) and several silicate glasses. The effect of compacting was studied by measuring the densities, dimensions, and x-ray diffraction patterns. A definite threshold pressure is observed in vitreous silica and silicate glasses, under which no effect takes place and above which the collapse takes place readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(149 citation statements)
references
References 5 publications
6
142
0
1
Order By: Relevance
“…As a large hydrostatic pressure leads to a transformation in chip formation zone from the single crystalline phase to the amorphous phase [69,70]. And the high hydrostatic pressure results in a plastic deformation of brittle materials [22][23][24]. This also proved that applying an external high hydrostatic pressure would increase the d c value so as to improve DMC performance.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As a large hydrostatic pressure leads to a transformation in chip formation zone from the single crystalline phase to the amorphous phase [69,70]. And the high hydrostatic pressure results in a plastic deformation of brittle materials [22][23][24]. This also proved that applying an external high hydrostatic pressure would increase the d c value so as to improve DMC performance.…”
Section: Discussionmentioning
confidence: 68%
“…Indentation on the soda-lime glass at different loads using a Vicker's pyramid indenter indicated that above a certain critical loading cracking was favourable while below the critical loading plastic flow was possible [20]. Indentation method was also used to evaluate the plastic deformation of brittle materials at high hydrostatic pressure [21][22][23][24]. A schematic illustration is shown in Fig.…”
Section: Ductile Nature and Plasticity Of Brittle Materialsmentioning
confidence: 99%
“…However, during the rebound of the projectile, the densification partially recovered and then, as soon as the projectile left the surface of the glass, radial and lateral cracks formed, as would be expected from the elastic/plastic model given in §2b. The ring of material that detaches during the rebound of the impacting sphere had, in fact, piled up around the sphere, as if it flowed plastically [41], during the loading part of the impact (figure 5, frame 3) and then detached from the glass surface as the steel sphere started its rebound.…”
Section: Discussionmentioning
confidence: 99%
“…SiO 2 glass is compressible among silicates (or oxides) [4][5][6][7] because it has a structure with a significant amount of interstitial voids 8 . Elastic softening and permanent densification of SiO 2 glass under high pressure are interesting issues in physics and materials science [4][5][6][9][10][11][12] and closely related to deformation and compaction of these voids. Information on the pressure dependence of its structure and density is also important in geophysics, because glasses can be considered as the analogue material of melts 11,13 .…”
mentioning
confidence: 99%